PERKEMBANGAN MADRASAH SUATU TINJAUAN HISTORIS-POLITIS - Abdul Aziz Ahmad (Badan Litbang dan Diklat Kementerian Agama RI, 2006)
Politically, educational position of madrasah (Islamic institution of learning) has been relatively powerful although its function is complementary to school education. However, problematic complexities faced by the madrasah nowadays still needs a long political struggle to make madrasah capable of running its function well and also keeping itself as a relatively original native religious institution constructed by long historic struggle of the moslem community. It is necessary for both madrasah and government as its protector to be aware of not only for the benefit of madrasah itself and a feeling of regret if madrasah should be disappeared, but also to guarantee the availability of educated and competitive human resources of the madrasah at both the national and international level. By using politico-historical perspective, this article tries to unpack and explicate what and how Madrasah as the religious-education institution in Indonesia.